Sources of the self - "Taylor, Charles" (Cambridge, 2006)
'Most of us are still groping for answers about what makes life worth living, or what confers meaning on individual lives', writes Charles Taylor in Sources of the Self. 'This is an essentially modern predicament.' Charles Taylor's latest book sets out to define the modern identity by tracing its genesis, analysing the writings of such thinkers as Augustine, Descartes, Montaigne, Luther, and many others. This then serves as a starting point for a renewed understanding of modernity. Taylor argues that modern subjectivity has its roots in ideas of human good, and is in fact the result of our long efforts to define and attain the good. The modern turn inwards is far from being a disastrous rejection of rationality, as its critics contend, but has at its heart what Taylor calls the affirmation of ordinary life. He concludes that the modern identity, and its attendant rejection of an objective order of reason, is far richer in moral sources that its detractors allow. Sources of the Self provides a decisive defence of the modern order and a sharp rebuff to its critics.
Keywords: Divinelife